Human sound localization: measurements in untrained, head-unrestrained subjects using gaze as a pointer - Populin, Luis C. (Experimental brain research, 2008)
Studies of sound localization in humans have used various behavioral measures to quantify the observers’ perceptions; a non-comprehensive list includes verbal reports, head pointing, gun pointing, stylus pointing, and laser aiming. Comparison of localization performance reveals that in humans, just as in animals, different results are obtained with different experimental tasks. Accordingly, to circumvent problems associated with task selection and training, this study used gaze, an ethologically valid behavior for spatial pointing in species with a specialized area of the fovea, to measure sound localization perception of human subjects. Orienting using gaze as a pointer does not require training, preserves the natural link between perception and action, and allows for direct behavioral comparisons across species. The results revealed, unexpectedly, a large degree of variability across subjects in both accuracy and precision. The magnitude of the average angular localization errors for the most eccentric horizontal targets, however, were very similar to those documented in studies that used head pointing, whereas the magnitude of the localization errors for the frontal targets were considerably larger. In addition, an overall improvement in sound localization in the context of the memory-saccade task, as well as a lack of effect of initial eye and head position on perceived sound location were documented.